Underestimated input of terrestrial dissolved organic carbon to the ocean - Yuanbi Yi; Andrew J. Tanentzap; Chen He; Julian Merder; Helena Osterholz; Hongyan Bao; Jeffrey A. Hawkes; Ruanhong Cai; Si-Liang Li; Quan Shi; Sheng Xu; Chuanlun Zhang; et al. (Proceedings of the National Academy of Sciences, 2025)
The contribution of terrestrial dissolved organic matter (DOM) to the ocean has been an enigma for decades. Tracking terrestrial DOM in the ocean has proven challenging due to factors such as the instability of terrestrial biomarkers, indistinguishable carbon isotopes from biogeochemical fractionation, and similar chemical composition between terrestrial and oceanic DOM. Here, we show that the terrestrial contribution to oceanic organic carbon pools is 1.7 to 2.5 times higher than previously assumed, highlighting the need to adjust global carbon cycle models. We derive these estimates by bridging high-performance liquid chromatography with ultra-high resolution mass spectrometry to investigate the presence of terrestrial molecules that are transported from rivers to the ocean and estimate their contribution to oceanic DOM. We identified 269 molecular formulae (MF) that are likely transported from land to the ocean. These formulae exhibited resistance to biological and photochemical degradation in incubation experiments, and were widely distributed in global rivers, marginal seas, and open oceans, suggesting that they are ubiquitous in inland and ocean waters and have a similar source. By relating the abundances of terrestrially derived MF to dissolved organic carbon concentrations, and radiocarbon measurements, we estimated that 16.7 to 25.0% of oceanic DOM is likely derived from rivers.